Effects of heavier hammer training on throwing distance and technique in the hammer throw - Hirose, K.; Ohyama Byun, K.; Fujii, H.; Aoki, K.; Maeda, K.; Kajitani, R.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this study was to investigate the cumulative effect of training with the heavier hammer (8.0 kg). Sixteen male hammer throwers were divided into a TR group (n=8) and a CT group (n=8). The TR group trained with the heavier hammer (8.0 kg) for 4 weeks. In order to investigate the effect of the training, tests were conducted before and after training. Utilizing three high-speed video cameras (300 fps), the three-dimensional coordinates of the hammer head and 25 landmarks on the body were obtained by the direct linear transformation method. The results showed that in the TR group, the throwing record was increased and the release velocity increased due to an increase of velocity increment during the turn. The maximum centrifugal force was increased in the all double support phase after training in the TR group. With regard to the lower limb joint angles, bending motion of the hip and the knee joint was emphasized after training in the TR group. These results suggest that throwing with the heavier hammer is an effective training method for improving the throwing distance, and for throwing action against the increased load during the turn phase.